PELATIHAN KONSELING DASAR BAGI KOMANDAN REGU YONIF 403/WP - Adi Heryadi; Arini Mifti Jayanti; Dian Juliarti Bantam (LPPM IST AKPRIND Yogyakarta, 2021)
Guarding border areas, assisting in handling natural disasters, forest fires and assisting POLRI tasks are part of the duties of the Indonesian Army. In carrying out its duties, YONIF 403 / WP, which is a combat unit under Korem 072 Pamungkas, is required to always be ready with various conditions in the field of assignment, including in the border area. As an ordinary human being, of course, the border condition which still lacks supporting facilities brings changes to the individual members of Infantry Battalion 403 / WP. Basic counseling training for team commanders is intended to prepare team commanders to be able to become counseling experts to assist members in need in the field of assignment. The training begins with a pre-test to determine the initial potential of the participants, then the training material consists of three sessions, namely an introduction to mental health, stages and the counseling process as well as sessions on ethics and communication in counseling. Participants attend practical counseling sessions with student clients and after that, feed back . The training was closed with a review and conclusion before the participants were given a post test to measure the results of the training that had been given. The results of the scale data analysis provided obtained a T value of -3665, Sig 0.002, which means that there is a very significant difference before and after the training. In conclusion, basic counseling training for the team commanders at Yonif 403 / WP were able to improve the team commanders' abilities in terms of counseling.